2012
DOI: 10.1093/jac/dks368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acquired  -lactamases on the evolution of spontaneous carbapenem resistance in Escherichia coli

Abstract: Plasmid-encoded β-lactamases, including non-ESBL enzymes, have a strong influence on the frequency and resistance level of spontaneous carbapenem-resistant mutants. The fitness cost associated with the loss of OmpC/OmpF in E. coli most likely reduces the survivability of porin mutants and could explain why they have not emerged as a clinical problem in this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 34 publications
10
66
0
Order By: Relevance
“…Our study showed that the Gly-63-Val substitution in OmpR renders the expression of ompC and ompF inactive. These results are in agreement with the in vitro studies of Tängdén et al and Adler et al, which demonstrated that a single-step EnvZ-or OmpR-inactivating mutation was enough to significantly increase the MIC for ertapenem due to a subsequent reduction of OmpC and/or OmpF of up to 90% (23,24). Our report provides further evidence for the clinical relevance of OmpR change in the emergence of ertapenem resistance among E. coli clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the Gly-63-Val substitution in OmpR renders the expression of ompC and ompF inactive. These results are in agreement with the in vitro studies of Tängdén et al and Adler et al, which demonstrated that a single-step EnvZ-or OmpR-inactivating mutation was enough to significantly increase the MIC for ertapenem due to a subsequent reduction of OmpC and/or OmpF of up to 90% (23,24). Our report provides further evidence for the clinical relevance of OmpR change in the emergence of ertapenem resistance among E. coli clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
“…An OmpR-inactivating mutation therefore might impact pathogen physiology and reduce bacterial fitness. Adler et al showed that OmpR inactivation caused a 20% reduction in growth rate (24). These results were in agreement with those obtained by Tsai et al, who showed that OmpK35/ompK36 porin deficiency in K. pneumoniae could decrease fitness and virulence (27).…”
Section: Discussionsupporting
confidence: 80%
“…Silver resistance was, however, easily induced in vitro, and in some cases this was associated with loss of porins and/or altered susceptibility to antibiotics. Loss of porins is known to cause decreased susceptibility to beta-lactams (18,32,40). A problematic decrease in susceptibility to piperacillin-tazobactam, one of the few treatment alternatives left in more severe infections caused by ESBL-producing E. coli, was noticed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of biochemical and genetic evidence supports the idea that many enzymes can catalyze adventitious secondary reactions (i.e., they have promiscuous activities), and that these activities are sometimes high enough to contribute to the fitness of the organism with the proper selective pressure and when overexpressed (Copley 2003;Khersonsky et al 2006;Khersonsky and Tawfik 2010). For example, various b-lactamases, with primary penicillin-hydrolyzing activities, can also contribute to decreased susceptibility toward other classes of b-lactam antibiotics Adler et al 2013). Patrick et al (2007) identified a number of E. coli genes that, when overexpressed, could complement the auxotrophy caused by lack of another gene.…”
Section: Innovationmentioning
confidence: 99%